KARAKTERISTIK FISIK TEMPAT TINGGAL LAYAK PENDUDUK LANJUT USIA DI KOTA YOGYAKARTA - Purnama Sanjaya, Fransisca Livia; Swasto, Deva Fosterharoldas (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2024)
The issue of an ageing population has become a global concern, including in Indonesia. The Special Region of Yogyakarta (DIY) ranks the highest in the number of elderly residents, with over 10%, most of whom live in urban areas, including the City of Yogyakarta. This city has been assessed for its suitability as an age-friendly city based on a study conducted by SurveyMETER and the Center for Ageing Studies at the University of Indonesia in 2013. The study found that Yogyakarta City is not yet friendly to the elderly. On the other hand, a study by Wighnanda (2016) stated that this city is desirable for retirees, and a survey by GoodStats (2022) indicated that the city is a popular choice for Indonesians to enjoy their retirement. These two statements raise questions about the physical characteristics of suitable housing from the perspective of elderly residents in Yogyakarta City. This study was conducted in Jatimulyo Baru Housing, Wirosaban Village, and Budhi Dharma Elderly Home. The research used a qualitative inductive approach. The data collection method consisted of two parts: primary data collection through observation and interviews, and secondary data collection by gathering information from institutions and the internet. The data analysis method used was qualitative descriptive analysis. The results showed that the physical characteristics of suitable housing from the perspective of elderly residents in Yogyakarta City include proximity to facilities, a clean, safe, and quiet environment, normal housing density, and environmental design that accommodates the mobility of elderly residents. Each of the three research locations had different specific characteristics. The conditions in Yogyakarta City are not yet entirely suitable for elderly residents.